Re-reading the Protagonist of Nemesis in the Mirror of the Myth of Sophocles’ Oedipus Rex - پدرام لعل بخش (Naqd-i Zabān va Adabīyyāt-i Khārijī, 2017)
The present study focuses on Bucky, Philip Roth’s protagonist in Nemesis, to analyze and criticize this character in the mirror of the myth of Sophocles’ Oedipus Rex. As such, the researcher tries to followSteven Totosy de Zepetnek’s theory of Comparative Study to explore the howness, not whatness, of the relations between the two works and create a dialogical space to scrutinize and delineate the existing differences and similarities. The findings of this study show that Roth rewrites Sophocles’ Oedipus Rex that is, itself, a proof of the overwhelming omnipresence of myths in our life. Furthermore, it seems that in adapting and recreating the myth of Oedipus, Roth has attempted to emphasize the vulnerability of mankind against the unbending power of fate in 21th century and in an era when man seems to be very proud of his scientific and technological advancements.